Adubação e assimilação de nitrogênio em duas espécies de fisális - Passos, Amanda Izabel dos (2013)
The genus Physalis belongs to the Solanaceae family and has about 120 species , widely distributed in tropical and subtropical regions . Among extant species , we chose to work with Physalis peruviana and P. pubescens , the first due to its use for productive purposes , and second , to have potential for production , but not be exploited due to be considered a weed plant . Assuming there are no studies on fertilization for the two species and that this nutrient is one of the most limiting to the development and production of plants , the objectives of this study were to evaluate the agronomic aspects of plants of P. peruviana and P. pubescens and check the activity of nitrate reductase and chlorophyll contents of the two species under different nitrogen levels . The experimental evaluation of the agronomic aspects was developed in a greenhouse using two species of physalis , five N rates : 0, 200, 250, 300 and 350 kg ha- 1 and in all treatments were 600 and 300 kg ha- 1 P and K,respectively. The experiment contained 7 replications per treatment in a randomized design. The variables studied were plant height, dry matter of roots and shoots , number of branches , root length , production and average fruit weight . P. pubescens showed greater response to nitrogen for all variables except number of branches and dry weight of shoots, showing that this species has a large productive potential . In the second experiment, we evaluated the activity of nitrate reductase and the content of chlorophyll a, b and total by biochemical method and portable meter in two species subjected to three nitrogen levels: 0, 150 and 300 kg ha- 1 . The seedlings were placed in plastic cups with commercial substrate, which were added the respective doses of nitrogen, phosphorus and potassium ( 600 and 500 kg ha- 1 for all treatments ) , in addition to the variables described above was also performed protein analysis. The experimental design was completely randomized with six replications and analyzes were made one month after fertilization The increase of N caused an increase in the levels of chlorophyll and protein and reduced enzyme activity in both species, with the highest dose P. peruviana highest values obtained in all cases .